Digital erasure: How social media platforms are silencing Palestinians in 2024 - Walid El Houri (Global Voices, 2025)
From shadow bans to account removals, tech platforms are censoring Palestinian speech while ignoring hate speech by Israeli figures.
Palestine (Permanent Observer to the UN)